The psychological impact of the media on promoting societal peace in the liberated areas, the city of Tal Afar as a model - Mortada Kazem (University of Mosul-college of Basic Education, 2024)
The media has a large and important role in consolidating ideas and mental images among the public and revealing realistic facts. The media has a role in promoting and preserving lofty values. The media has significant psychological effects in times of peace and war, which can be used to serve peaceful coexistence. Community peace can be enhanced through the media and various information activities. Media outlets committed to professional standards and ethics have, through their various means and activities, strengthened societal peace in the liberated areas. The residents of the liberated areas, especially Mosul and Tal Afar, are an example of being exposed to two types of media messages. The first is inflammatory, used by ISIS terrorist gangs during their occupation of the city, affecting the souls of the residents. The second is supportive of societal peace, which has a greater and broader impact as it is close to reality and reinforces human common sense and lofty values. The media outlets supporting the security forces that liberated the city of Mosul worked to greatly enhance societal peace by broadcasting targeted messages and stating the facts accurately despite the war conditions. They highlighted the sound and dedicated dealings of the security forces of all types and formations with the civilian residents of the city, which also contributed to consolidating peace. community among the population.